Pouvoir d’agir et capacités d’agir : une perspective méthodologique ? - Catherine Gouédard; Pierre Rabardel (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper presents a methodological framework for assessing the capacity and power to act of different agents within an organization, in terms of health, safety and working conditions. The innovation we propose is the development of an assessment instrument, “Questioning the Power to Act” (QPA), a tool based on a questionnaire from Quebec, designed to measure the power to act in different areas and use questioning techniques to make a qualitative analysis of the capacity and power to act of the agents involved. The preparatory research raised some questions as to the relationship between the pre-established categories of the original questionnaire and the categories the QPA instrument would propose for assessing individuals’ capacity and power to act. Our analysis showed cross links, but the categories remain based on two distinct theoretical frameworks and are not identical. Before concluding, we discuss the potential advantages to be gained from use of the QPA as an interview support and time analysis tool, its interest and its limits.